GLIOBLASTOMA MULTIFORME: A BRIEF LITERATURE REVIEW - Fernandes Moniz, Yasmim (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
The objective of this article is to review the current state of knowledge about glioblastoma multiforme.  Gliomas originated in astrocytes can be classified into four types: Pilocytic Astrocytoma, Fibrillary Astrocytoma, Anaplastic Astrocytoma and Glioblastoma Multiforme. Glioblastoma Multiforme is the most malignant and aggressive type of these. The risk factors for this tumor are still poorly understood, but it has been proven that ionizing radiation can be one of them. The diagnosis is made through the analysis of the critical manifestations and with complementary examinations such as computed tomography and magnetic resonance imaging. The treatments used against this type of tumor are maximum tumor resection, radiotherapy, chemotherapy, Tumor-Treating Fields, Bevacizumab, Oncolytic Viruses. Although there are several types of treatment, the prognosis of this tumor remains limited. More studies are needed tob investigate the effectiveness of the treatments used, as well as the access of the general public to these treatments in the public health system.